PWE-099 Contribution of surgery and disease subtype to health related quality of life in patients with locally advanced and recurrent colorectal cancer. (28th May 2012) - Vaughan-Shaw, P G; Sreekumar, R; Curtis, N J; Bullock, M D; Armstrong, T; Bateman, A; Bryant, T; Knight, J S; Hayes, M C; Lockyer, R W; Phillips, M; Mirnezami, A H
Abstract : Introduction: Management of patients with locally advanced (LA) and locally recurrent (LR) colorectal cancer is challenging, with patients frequently requiring complex multimodality interventions. Despite increasing emphasis on evaluation of health related quality of life (HRQoL) in patients having complex interventions, HRQoL information on patients with LA and LR colorectal cancer is sparse. The aim of this study was to prospectively assess outcome measures and HRQoL in a cohort of patients with LA and LR colorectal cancer at our institution. Methods: LA disease was defined as tumour requiring extended multi-visceral resection in the abdomen or pelvis to achieve an R0 resection. 45 consecutive patients were prospectively assessed over a 2-year period. Demographic, treatment, and cancer-related outcomes were recorded on all patients. Pelvic disease was staged using Leeds and Royal Marsden Hospital classification systems. HRQoL was prospectively evaluated using the EORTC generic and disease specific instruments QLQ-CR30 and QLQ-CR29. Results: Median age was 69 (range 46–89) and 60% were male (27/45). There were 25 cases of LA disease and 20 LR cases. 35 patients underwent surgery while 10 patients had non-surgical palliation. R0 resection rate was 94%. HRQoL data were available on 41 patients. Median global health status was 65 (95% CI 55.5 to 74.1), physical functioning 77 (95% CI 69.9 to 84.5), and social functioning 72 (95% CI 60.3 to 83.8), which compared favourably with published EORTC reference values. Global health status and pain were significantly better in patients having surgery compared to non-surgical palliation (p<0.0001 and p<0.0004). Assessment of individual function and symptom scales revealed no significant difference in HRQoL between LA and LR except for greater buttock pain in patients with LR disease. Conclusion: In carefully selected patients, HRQoL after radical multimodality treatment for LA and LR colorectal cancer is acceptable, and gives better results than palliation. Competing interests: None declared.